Deliverable 5.9 Data integrated from existing repositories V2 - Schewe, Ingo; Caumont, Hervé; Ors, Fabien; Morvik, Arnfinn; Thorne, Peter (Zenodo, 2021)
The INTAROS project develops an integrated Arctic Observation System (iAOS) by extending, improving and unifying existing systems in the different regions of the Arctic. Within INTAROS, WP5 (Data integration and management) is tasked with designing and implementing evolution of the cloud platform with geo statistical tools for services as part of the iAOS. Partners in Task 5.3 are in charge of data integration from existing repositories, along with metadata, so that it is findable and exploitable by iAOS applications, and well referenced by the iAOS Portal and the INTAROS Data Catalogue. In particular, identification of the online data access points and the related protocols are offered to make the data accessible for use in the iAOS Showcase application services, as well as from other applications in WP6 which can utilize these data. Deliverable D5.9 describes the work done in Task 5.3 with respect to identifying and clarifying the technical requirements for data integration of existing data repositories, and gives examples of such integrations. Section 2.1 provides information on the growth of registered datasets in the INTAROS Data Catalogue as of 22nd April 2021 compared to 1st December 2019. A summary of to what extent the original plans for integration of data repositories in Task 5.3 have been achieved is given in Section 2.2. AWI / Terradue conducted an email campaign to partners in order to identify which datasets are planned to be registered in the INTAROS Data Catalogue (Section 2.3). Section 3 describes relevant data repositories which in some cases are linked to the iAOS cloud platform and in other cases listed as potential source of data (when an actual integration into data processing applications was performed as part of other INTAROS tasks, the mention “iAOS Application” is added along with the reference to it). Section 4 describes the data sources for selected iAOS Showcase applications, the data needed by application developers, and how the foreseen output data products could be used. In ...